Information And Communication Technology And Government During Covid-19. - Sakachep, Mante (International Journal of Psychosocial Rehabilitation, 2020)
Information and Communications Technology (ICT) has emerged as one of the key players in Fighting the COVID-19 situation in India. The unprecedented crisis due to COVID-19 has Accelerated the process of digitalization of many services and businesses including healthcare Services, education, online delivery of goods and services, online payments, and work from Home. The study also try to find out how the digital technologies are playing a key role in keeping our societies functional in this time of lockdowns and quarantines. The COVID-19 pandemic has compelled everyone to take a Digital approach to being an employee, friend, or family member. The paper also examine how government play an important role for the people during the global crisis. The study also focus on how government still continue to work during pandemic through virtual meet.